Obscure Gastrointestinal Bleeding: An Approach to Management. (1st February 2000) - Marshall, JK; Lesi, OA; Hunt, RH
Abstract : Obscure gastrointestinal bleeding provides an uncommon but frustrating and resource-intensive challenge for clinicians. Such patients hemorrhage recurrently from sites within the gastrointestinal tract that are not detected by routine endoscopy or radiography, and require a special diagnostic approach to localize or exclude less common bleeding sources such as small bowel angioectasia or neoplasia. The differential diagnosis of obscure gastrointestinal hemorrhage is discussed, and the performance of available endoscopic, radiological and surgical diagnostic tools including enteroscopy are examined critically. A stepwise management algorithm that progresses from the history and physical examination to surgical exploration is offered to facilitate early and efficient diagnosis.